Problematic internet use as a predictor of emotional self-regulation, online risk behaviors and tolerance to diversity in Spanish adolescents - Duch-Ceballos, Carla; Calatrava, María; Rodríguez-González, Martiño; Schweer-Collins, Maria (Anales de Psicología / Annals of Psychology, 2025)
Problematic Internet Use (PIU) is characterized by a high frequency and intensity of Internet connection and a high degree of interference in daily life. Although several studies link PIU with poorer emotional regulation, none have investigated emotion regulation from a family systems perspective. The present study explored the relationship between PIU and online risk behaviors, differentiation of self and tolerance of diversity, in Spain. This is a cross-sectional study on 361 Spanish adolescents (48.2% men, 51.8% women) between 14 and 21 years old participated. Findings showed statistically significant differences in key variables based on sex and family structure. PIU predicted poorer differentiation of self, greater risky behaviors, and a lower tolerance of diversity. Implications for practice and suggestions for future lines of research are discussed.